(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: The recognition of unusual canals configurations and variations are essential for successful endodontic diagnosis and treatment. This study was aimed to investigate the occurrence of C- shaped root canal in Malaysian population. Design: This is an in vitro study whereby 241 extracted human first and second molars with intact root were collected from several dental clinics in Malaysia. Materials and Methods: The roots were sectioned at three levels: subpulpal level, 3mm from apical tip and middle level between the first and last level. The appearance of the root canal sections were assessed using stereomicroscope (Leica, Germany) and pictures were taken. Data were analyzed statistically using Fishers Exact and Binomial test with p<0.05 indicates statistically significant difference. Results: The occurrence of C- shaped canal among molars collected is 3.73%. Hundred percent of the molars with C- shaped root canal configuration are mandibular molars and 77.8% are belonged to Chinese racial. Conclusion: The findings show that C- shaped root canals do occur among Malaysian people especially Chinese racial. Besides, all the teeth that possess C- shaped root canal configuration are lower molars. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 286-290 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15427